(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: The goal is to develop a cross-sectoral, innovative, inclusive, and impactful gender equality plan for Lithuanian Sports University (LSU) that explicitly addresses the issues of gender-based violence and sexual harassment at the university and in the sports sector. Project Description: Development. The SUPPORTER project at the Lithuanian Sports University was launched in 2023 by analysing the project goals and objectives and adapting them to the context of the university’s studies, research, and community activities. The main focus was on promoting an institutional, inclusive, and sustainable culture of change, addressing issues caused by inequality and promoting gender equality in the context of sport, including GBV (gender-based violence) in sport and academia. LSU researchers, lecturers, student representatives, and partners from sports organisations participated in the development of the project. Implementation. During the implementation of the SUPPORTER project, LSU organised trainings, seminars, and discussions for students, staff, and external stakeholders. Cooperation was also carried out with local communities and other participants in the education sector, in order to spread the project ideas wider than just within the university. Evaluation. The quality of the project implementation was assessed by collecting feedback from participants after the events, conducting questionnaires and discussions with students, staff, and external stakeholders. The evaluation also included the integration of project activities into study modules, research and the possibility of continuity of long-term initiatives. Dissemination. The results of the SUPPORTER project at LSU were actively disseminated both within the university and nationally. Information was shared through the university’s website, social networks, public events, and the company. The project experiences were presented at international conferences, and it is also planned to integrate the accumulated experience into new scientific research and study programmes, ensuring the continuity and development of activities. Conclusion: The SUPPORTER project at LSU has developed a Gender Equality Plan, organised trainings and discussions in a safe and inclusive physical activity environment. This has expanded knowledge about the importance of social inclusion in health-enhancing physical activity, encouraged the application of new interdisciplinary teaching methods, and practically strengthened the LSU community initiatives to promote a safe environment.